Reliability of an Observational Biomechanical Analysis Tool in Adolescent Baseball Pitchers - Steven F DeFroda; Dai Sugimoto; Steven J Staffa; Donald S Bae; Ellen Shanley; Charles A Thigpen; Peter K Kriz (International Journal of Sports Physical Therapy)
# Background